2021
DOI: 10.3390/ijerph18189577
|View full text |Cite
|
Sign up to set email alerts
|

From Burden to Depressive Symptoms in Informal Caregivers during the COVID-19 Pandemic: A Path Analysis

Abstract: Background: The objective of this study was to assess the complex relationship between the multiple determinants of the caregiving process, the caregiver burden, and depression during the COVID-19 pandemic in Serbia. Methods: A cross-sectional study was conducted on a nationally representative sample (n = 798) during the COVID-19 pandemic in Serbia from March to September 2020. A nine-section questionnaire designed for this study included the characteristics of caregivers, characteristics of care and care reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
3
7
0
Order By: Relevance
“…In our study, the ICs of older people who provided more demanding and intensive care experienced a higher subjective burden of care. These findings are consistent with the results of several other studies [ 18 , 43 , 66 , 70 , 91 , 99 , 124 , 125 ] that found a high and increased caregiver burden during the COVID-19 pandemic. A German study of 1000 ICs [ 66 ] found that 25.5% to 39.7% of ICs reported that their caregiving situations somewhat or greatly worsened during the COVID-19 pandemic, especially among those caring for a person with dementia or who normally relied on professional help.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the ICs of older people who provided more demanding and intensive care experienced a higher subjective burden of care. These findings are consistent with the results of several other studies [ 18 , 43 , 66 , 70 , 91 , 99 , 124 , 125 ] that found a high and increased caregiver burden during the COVID-19 pandemic. A German study of 1000 ICs [ 66 ] found that 25.5% to 39.7% of ICs reported that their caregiving situations somewhat or greatly worsened during the COVID-19 pandemic, especially among those caring for a person with dementia or who normally relied on professional help.…”
Section: Discussionsupporting
confidence: 93%
“…However, the researchers also suggested that ICs whose burden increased during the pandemic may have already exhibited risk factors for high caregiver burden prior to its onset. Studies from the Netherlands and Serbia [ 98 , 99 ] found that the declining health of ICs and care recipients during COVID-19 was related to an increased level of perceived burden of care. While several studies have examined specific individual characteristics of caregiving situations during the pandemic [ 12 , 18 , 20 , 25 , 43 , 44 , 67 , 68 , 69 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], only one study comprehensively examined the caregiving situation and care involvement [ 66 ], and the same study was the only one that examined the caregiving situation in relation to psychosocial burdens.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to hypotheses 3 and 4, concerning evidence of construct validity in caregivers of palliative care patients, it is confirmed that the scale shows statistically significant, positive and moderate–high relationships with caregiver burden levels and anxiety and depression scores, as well as statistically significant, negative and low relationships with family functioning, life satisfaction, resilience and psychological quality of life. Correlations of fatigue with caregiver burden and anxiety and depression have already been widely reported in the literature [ 1 , 18 , 33 , 64 ]. This evidence of convergent and divergent validity shows adequate construct validity with respect to other variables in the nomological network.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of fatigue in caregivers of palliative care patients using a validated tool will enable healthcare professionals to ascertain and specifically monitor their fatigue levels. It will also help in the evaluation of new interventions for preventing fatigue and improving the quality of life of these caregivers through an individualized and needs-based approach [ 27 , 33 ]. Further studies are needed using both quantitative and qualitative approaches to fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation